ICHI - Icelandic Crime Harm Index : preparation for implementing Crime Harm Index to Iceland - Haraldur Logi Hringsson 1980- (2019)
Verkefnið er lokað til 30.06.2021. The way crimes are measured in many societies across the world, including Iceland is to count them. However counting crimes suggests that all crimes are created equal. The Crime Harm Index is a new concept of looking at crimes from a harm point of view. By creating a base line for the severity of crimes, crimes be compared with the same unit but different weight, depending on their seriousness or harm that these crimes inflict upon individuals and or society. The original Crime Harm Index comes from Cambridge University, and they use sentencing guidelines for creating the weight of offences. This thesis aims to give an overview of the development and definition of a Crime Harm Index in different countries, such as New Zealand, Western Australia, Sweden and Denmark and to identify the benefits and challenges of developing a Crime Harm Index in Iceland. The Icelandic justice system is the closest to the Danish justice system: Denmark does not have sentencing guidelines, but they use prosecutors’ guidelines instead. Having conducted a systematic review of the literature and conducted a focus group with a small group of police lawyers, it is recommended that Iceland develop a Crime Harm Index similar to the Danish model but based upon the legal system and uniqueness of Iceland. In Iceland there will also be an Appendix next to the first Crime Harm Index that would include proactive offences like traffic or drug offences, and later this will be included in the index. It is recommended that Iceland will go to prosecutors and ask them how many days in prison they would demand in court for a particular offence if; the offender is over 18 years old, it is the first offence and there are no mitigating or aggravating factors. This creates a weight that is then multiplied with the number of offences committed. The benefits are to find the power to reduce the number of offenders and victims. This harm approach does not replace other crime measurements but adds an additional lens on how ...